The Climax of the Bank War: Biddle's Contraction, 1833-34 - Meerman, Jacob P. (Journal of Political Economy, 1963)
Sir the project astonishes me.... We are again to see the drama which already in the course of the present century has passed before us, and closed in ruin. If the project shall be successful, we are again to see those paper missiles shooting in every direction through the country; a derangement of all value; a depreciated circulation; a suspension of specie payments; then a further extension of the same detestable paper; a still greater depreciation, with failures of traders and failures of banks in its train; to arrive at last at the same point from whence we departed in 1817.